1999
DOI: 10.1097/00007632-199901010-00008
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic Limitations of Posterior Decompression by Midsagittal Splitting Method for Myelopathy Caused by Ossification of the Posterior Longitudinal Ligament in the Cervical Spine

Abstract: Patients who exhibit significant risk factors for continued contact of the spinal cord should be morphologically considered for anterior decompression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(37 citation statements)
references
References 4 publications
0
37
0
Order By: Relevance
“…57 Furthermore, laminoplasty, specifically, has been correlated with progressive kyphosis and subsequent neurological deterioration at long-term follow-up, probably accounting for our findings of an increased recovery rate in the decompression and fusion population. 28,51 Although outcomes after laminoplasty for a large OPLL mass are poor, 32 previous studies have shown that higher preoperative lordosis is associated with better outcomes after laminoplasty in patients with a large OPLL mass.…”
mentioning
confidence: 62%
“…57 Furthermore, laminoplasty, specifically, has been correlated with progressive kyphosis and subsequent neurological deterioration at long-term follow-up, probably accounting for our findings of an increased recovery rate in the decompression and fusion population. 28,51 Although outcomes after laminoplasty for a large OPLL mass are poor, 32 previous studies have shown that higher preoperative lordosis is associated with better outcomes after laminoplasty in patients with a large OPLL mass.…”
mentioning
confidence: 62%
“…2,3 Previous studies evaluated these 2 factors independently, and, to the best of our knowledge, no report has analyzed them in 1 parameter. In the present study, we proposed a new index that can evaluate the cervical alignment and the OPLL size in 1 parameter.…”
mentioning
confidence: 99%
“…Studies have also found an association between depth of cervical lordosis and chronic headache 54, 55 . Several researchers have reported that neurologic improvement is associated with posterior shift of the spinal cord and for this to happen, lordotic alignment of the cervical spine is essential to allow the spinal cord to shift dorsally 46, 56, 57 .…”
Section: Discussionmentioning
confidence: 99%